Adverse Weather Impact on Road Crashes: A Comparative Analysis Between Barishal and Khulna Divisions - Hasan, Md Fuad; Mahmud, S M Sohel; Akter, Ayesha; Sakib, Faisal Mahmud (Journal of Engineering Science, 2025)
Bangladesh faces a troubling surge in road crashes, prompting the research on contributing factors. Research emphasizes adverse weather, particularly rainfall, temperature fluctuations, and visibility, as key catalysts. Investigating Khulna and Barishal divisions from 2018 to 2022, this study rigorously employs matched pair analysis. It aims to reveal the intricate interplay between adverse weather and crashes, assessing impacts on frequency, injuries, and fatalities. Findings show robust correlations between adverse weather, like intense rainfall and poor visibility, and increased crash, injury, and fatality rates. In Barishal, light rainfall (1-2 mm) offers a safety advantage, with a 14.59% lower injury rate, while moderate rainfall (3-7 mm) elevates risk with a 13.60% injury rate. Heavy rain (8-12 mm and ≥26 mm) significantly raises crashes and fatality rates, peaking at 41.38% fatalities. Conversely, Khulna responds differently. Even minor rain increments (1-2 mm) increase crashes and fatality rates to 11.5% and 20.9%, respectively. Higher rainfall (8-12 mm) links to intensify crashes and fatality rates, while 26-50 mm and ≥50 mm ranges maintain stable rates but heighten injuries. Wet roads (>2.5 mm water depth) associate with reduced crashes (7.2%), fatality (5.1%), and injury (7.6%) rates. The study conducts significance tests (t-test) in Khulna and Barishal Divisions, revealing in Khulna a substantial correlation between heavy rainfall (>12.5 mm) and increased crash risk and severity. In Barishal, wet road conditions significantly correlate with raised crash risk. Moderate temperatures (15-30°C) see a crash rate of 17.48 per day, with 45.47% injuries and 14.86% fatalities. Above 30°C, crashes decrease to 14.99 per day with lower injury and fatality rates. In Khulna, colder (<15°C) temperatures have higher crash rates (18.18%) with significant injuries (5.45%) and fatalities (18.18%). In 15-30°C range, crashes decrease, but injury rates rise. Visibility consistently affects road safety in both divisions. Improved visibility reduces crashes, fatality, and injury rates. This study made use of weather data from Bangladesh Meteorological Department (BMD) and reported crash data collected from Accident Research Institute (ARI). The study places a strong emphasis on preventative actions to lessen weather-related road safety risks, improving empirical understanding of the impact of weather dynamics on road crashes in Bangladesh, supporting targeted initiatives for road safety, and guiding policy decisions. Journal of Engineering Science 15(2), 2024, 89-103